Analysis Of Handling Practices On Corruption Crime By Police (Case Study In Special Criminal Investigation Police Directorate Of Central Java) - Muhamad Riyadi Putra; Gunarto Gunarto (Magister of Law, Faculty of Law, Universitas Islam Sultan Agung, 2019)
Corruption is categorized as an extraordinary crime are not only a disaster for the national economy, but also a violation of the rights of social and economic rights of the people. Police officers as part of the legal system, the role is very particularly important in law enforcement anti-corruption law enforcement. Police as a sub-system of the Criminal Justice System, authorized to perform the duties of investigation of all criminal offenses in accordance with the Criminal Procedure Law and the regulations of other legislation including corruption cases, in addition to law enforcement agencies such as the Attorney and the Corruption Eradication Commission. The problem in this paper is handling practices of corruption by Indonesian National Police (INP) as the law enforcement sector which has authority in law enforcement against those specific criminal offense. The role of the police in handling corruption is a duty of inquiry and investigation against corruption by the Criminal Code, Act No. 2 of 2002, Act No. 31 of 1999 jo. Act No. 20 of 2001 and Presidential Instruction No. 5 of 2004. The function and authority of the Police in the investigation of corruption cases, the police play a very large in the case of law enforcement corruption. One of the functions of the Police in the investigation is the arrest, detention, search, and seizure. Keywords: Management; Crime; Corruptio; Police.